Proximal Splenorenal Shunt Surgery for Bleeding Gastric Varices in Non-Cirrhotic Portal Hypertension - Anand, Utpal (Cureus, 2020)
Background The optimal management of gastric variceal bleeding in patients with non-cirrhotic portal hypertension (NCPH) is debatable due to the lack of data from large randomized controlled trials. Here we present our experience on proximal splenorenal shunt (PSRS) surgery in NCPH patients with bleeding gastric varices. Methods Over a five-year period, a total of 25 PSRS surgeries were performed and data was collected prospectively. Nineteen extrahepatic portal vein obstruction (EHPVO) and six non-cirrhotic portal fibrosis (NCPF) patients with bleeding fundic or isolated gastric varices and normal liver function were included. The collected data was analyzed retrospectively. Results Of the 25 patients who underwent PSRS five were lost to follow-up. Twenty patients (80%) were followed up for a median of 3.4 (1-5) years. Gastric variceal regression was noted in all 20 patients with the disappearance of varices in eight patients. On follow-up, shunt thrombosis was noted in four (20%) patients of whom, two had rebleeding between six months and three years after shunt surgery. Conclusion PSRS was effective in controlling gastric variceal hemorrhage in 92% (23 of 25) of patients with preserved liver function.